2005
DOI: 10.3200/genp.132.4.335-346
|View full text |Cite
|
Sign up to set email alerts
|

Second-Order Judgments About Judgments of Learning

Abstract: ABSTRACT. The authors explored the relations between predictions of the likelihood of recalling studied items (called judgments of learning, or JOLs) and second-order judgments (SOJs), in which one rates confidence in the accuracy of each JOL. Each participant studied paired-associate items and made JOLs. A given JOL was either immediate or delayed and was followed immediately by an SOJ. After all items were studied and judged, paired-associate recall occurred. The incorporation of SOJs into this standard meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
59
0
4

Year Published

2012
2012
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(74 citation statements)
references
References 20 publications
6
59
0
4
Order By: Relevance
“…In addition, the authors asked for second-order judgments (SOJs) to assess the students' awareness of their metacognitive monitoring ability. SOJs are confidence judgments for previously given performance judgments (Dunlosky, Serra, Matvey, & Rawson, 2005) and can be regarded as meta-monitoring (Dunlosky et al, 2005) or meta-metacognitive judgments (Buratti & Allwood, 2012). Confirming the results by Kruger and Dunning (1999), Miller and Geraci found that low-performing students' performance judgments were too high in comparison with their actual performance.…”
Section: Metacognitive Monitoring Ability and Performancesupporting
confidence: 56%
See 1 more Smart Citation
“…In addition, the authors asked for second-order judgments (SOJs) to assess the students' awareness of their metacognitive monitoring ability. SOJs are confidence judgments for previously given performance judgments (Dunlosky, Serra, Matvey, & Rawson, 2005) and can be regarded as meta-monitoring (Dunlosky et al, 2005) or meta-metacognitive judgments (Buratti & Allwood, 2012). Confirming the results by Kruger and Dunning (1999), Miller and Geraci found that low-performing students' performance judgments were too high in comparison with their actual performance.…”
Section: Metacognitive Monitoring Ability and Performancesupporting
confidence: 56%
“…To that end, local judgments were analyzed with reference to the classification system of signal detection theory. Until now, previous research on local (second-order) judgments had used confidence scales rather than dichotomous items for performance judgments (Buratti & Allwood, 2012;Dunlosky et al, 2005). This made it impossible to categorize performance judgments according to signal detection theory.…”
Section: Discussionmentioning
confidence: 99%
“…When we are prompted to make judgements on how we perceive our ability, how well we know something or how well we have performed a particular task, the judgements we report are called metacognitive judgements (Rosenthal, 2000;Dunlosky et al, 2005;Koriat and Bjork, 2005;Fernandez-Duque and Black, 2007). Metacognitive judgements have been extensively investigated partially due to the fact that mastery of the skill of accurately making them may result in the effective management of self-regulated study, which is necessary in a tertiary environment where an autonomous approach to studying is required (Dunlosky et al, 2005).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Metacognitive judgements have been extensively investigated partially due to the fact that mastery of the skill of accurately making them may result in the effective management of self-regulated study, which is necessary in a tertiary environment where an autonomous approach to studying is required (Dunlosky et al, 2005). Metacognition refers to the knowledge and experiences we have about our own cognitive processes (Flavell, 1979).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Arguing against the double curse account, Miller and Geraci (2011) provided evidence that functional overconfidence in low performing students is most likely not because they are unaware of their own metacomprehension deficits. In their findings, while low performing students were certainly more functionally overconfident in their prediction judgments, they were also less subjectively confident than high performing students in the accuracy of those prediction judgments of test performance, which suggests that these students are somewhat aware of their own poor metacognitive calibration (also see Dunlosky, Serra, Matvey, & Rawson, 2005). The present study had two specific aims: first, to assess which of the aforementioned views applies when students are making after-the-fact, postdiction judgments; second, to assess whether such functional and subjective confidence changes over time across several exams in a semester-long class.…”
Section: Introductionmentioning
confidence: 99%